Cobalt wire preparation method for self-powered neutron sensitive element

Through cobalt powder reduction treatment, vacuum induction smelting and multiple mechanical processing, cobalt wires with high purity and excellent performance are prepared, which solves the problem of unstable performance of cobalt wires in the prior art and meets the high performance requirements of neutron-sensitive components of nuclear reactors.

CN118272678BActive Publication Date: 2025-04-08CHONGQING MATERIALS RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410352195.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-26
Publication Date
2025-04-08
Estimated Expiration
2044-03-26

AI Technical Summary

Technical Problem

In the prior art, when preparing cobalt wire, it is difficult to ensure the stability of the purity, impurity element content, ellipticity, surface quality and mechanical properties of the cobalt wire, resulting in poor sensitivity, measurement accuracy and service life of cobalt self-energy neutron sensitive elements.

Method used

Cobalt wires with a diameter of 1.00mm to 2.00mm can be prepared by steps such as cobalt powder reduction treatment, mixing and press forming, vacuum induction smelting, forging, rotary forging, drawing, electrolytic polishing and annealing. Through these steps, oxygen elements can be effectively removed, powder molding capacity can be improved, temperature and impurity dispersion can be controlled, and the high purity and excellent performance of cobalt wire can be ensured.

Benefits of technology

The cobalt wire has achieved high purity (≥99.95%), low impurity element content (≤30ppm), high tensile strength (≥900MPa), high elongation (≥6%) and excellent surface quality, which meets the performance requirements of emitter materials for self-sustaining neutron-sensitive components of EPR nuclear reactors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118272678B_ABST
    Figure CN118272678B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a cobalt wire for a self-powered neutron sensitive element, comprising the following steps: 1) cobalt powder reduction treatment; 2) mixing and pressing; 3) vacuum induction melting; 4) forging, rotary forging, drawing; 5) electrolytic polishing and annealing. The method of the present invention can prepare a cobalt wire with a diameter of 1.00 mm to 2.00 mm, the purity of the cobalt wire is ≥99.95%, the content of each element of boron, cadmium, chromium, copper and silicon that are not resistant to radiation in the cobalt wire is ≤30ppm, the accuracy of the cobalt wire ellipticity reaches ±0.003mm, the surface roughness is ≤Ra1.6μm, the tensile strength is ≥900MPa, and the elongation is ≥6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and in particular relates to a method for preparing a cobalt wire used for a self-powered neutron sensitive element. Background Art

[0002] Fast response cobalt self-sufficient neutron sensitive element is the key basic component for neutron measurement and control of EPR nuclear reactor. As the key material of emitter for self-sufficient sensitive element, the purity, impurity element content, wire diameter uniformity, mechanical properties and surface quality stability of cobalt wire directly affect the key performance of cobalt self-sufficient neutron sensitive element, such as sensitivity, measurement accuracy and service life. Cobalt wire is required to have a purity of not less than 99.9%, and the content of impurity elements such as boron, cadmium, chromium, copper and silicon that are not resistant to radiation in the cobalt wire is not more than 30ppm. The ellipticity of the cobalt wire does not exceed 0.01mm, the surface roughness is not more than Ra1.6μm, the tensile strength is not less than 900MPa, and the elongation is not less than 6%.

[0003] At present, cobalt wire is prepared by common hot deformation processing (forging, hot drawing, etc.) or cold processing (cold forging, cold drawing, etc.) processes. These methods will lead to problems such as low purity of cobalt wire, high content of impurity elements, difficult to control ellipticity, unstable surface quality, poor product consistency, etc. Among them, when hot deformation is used to process cobalt wire, since cobalt belongs to a body-centered cubic structure, there is a plastic-brittle transition phenomenon during the hot deformation process. It starts to oxidize when it exceeds 300°C. Continued heating will cause cobalt to react with oxygen and show brittleness, making high-temperature deformation processing of cobalt wire extremely difficult; among them, when cold processing cobalt wire is used, since the hardness of cobalt is very high, the surface quality of the cobalt wire is easily damaged during the cold processing process, and it is difficult to ensure the uniformity and consistency of the emitter. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing cobalt wire for self-powered neutron sensitive elements in view of the deficiencies of the prior art. By adopting the method of the present invention, cobalt wire with a diameter of 1.00 mm to 2.00 mm can be prepared, the purity of the cobalt wire is ≥99.95%, the content of each element of boron, cadmium, chromium, copper and silicon that are not resistant to radiation in the cobalt wire is ≤30ppm, the accuracy of the ellipticity of the cobalt wire reaches ±0.003mm, the surface roughness is ≤Ra1.6μm, the tensile strength is ≥900MPa, and the elongation is ≥6%.

[0005] The object of the present invention is achieved in that:

[0006] A method for preparing a cobalt wire for a self-powered neutron sensitive element comprises the following steps:

[0007] 1) Cobalt powder reduction treatment:

[0008] The cobalt powder is loaded into a molybdenum boat and reduced under hydrogen conditions at a reduction temperature of 350 to 550° C. for a holding time of 3 to 5 hours to obtain reduced cobalt powder;

[0009] 2) Mixing and pressing:

[0010] The reduced cobalt powder is added to the zirconium powder for high-energy ball milling, and then pressed into shape after mixing, wherein the amount of the zirconium powder added is 0.1-0.3% of the weight of the cobalt powder;

[0011] 3) Vacuum induction melting:

[0012] The formed cobalt is placed in a vacuum melting furnace, the melting current is adjusted in the range of 0 to 30A, the current adjustment interval is 2 to 5 minutes, after the cobalt is completely melted, electromagnetic stirring is performed for 2 to 5 minutes, and the ingot is formed into a cobalt ingot;

[0013] 4) Forging, rotary forging, drawing:

[0014] The cobalt ingot is forged into a cobalt metal rod, which is then rotary forged into a cobalt bar. After the surface of the cobalt bar is pretreated, the cobalt bar is drawn into a cobalt wire, which is then annealed.

[0015] 5) Electrolytic polishing and annealing:

[0016] The annealed cobalt wire is electropolished and annealed.

[0017] The purity of the cobalt powder is ≥99.95%, the Fisher particle size is 15-35 μm, and the particle size is normally distributed; the purity of the zirconium powder is ≥99.99%.

[0018] The flow rate of the hydrogen in step 1) is 4 to 8 L / min.

[0019] Step 2) During the high-energy ball milling, the ratio of the mixed material to the steel ball is 1:0.3, the high-energy ball milling time is 12 to 18 hours, and the rotation speed is 70 to 130 r / min;

[0020] The pressing pressure is 150-200 MPa, and the pressure is maintained for 15-30 seconds.

[0021] Step 3) The crucible is a zirconia crucible;

[0022] The vacuum melting furnace is firstly purged with argon gas and then evacuated to a temperature of <1×10 -3 Pa;

[0023] The diameter of the cobalt ingot is 30-50 mm.

[0024] Step 4) The heating temperature of the forging is 800-1000° C., the holding time is 8-15 min, the initial forging temperature is 900-1000° C., the final forging temperature is 650-750° C., and the deformation amount of each forging pass is 20-30%;

[0025] Before the cobalt ingot is heated, a layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is applied on its surface;

[0026] The diameter of the cobalt metal rod is 13-15 mm.

[0027] Step 4) The heating temperature of the rotary forging is 800-1000°C, the holding time is 5-10 minutes, and the deformation amount of each pass is 15-20%;

[0028] Before the cobalt metal rod is heated, a layer of high temperature resistant and oxidation resistant organic silicon lubricating coating is applied on its surface;

[0029] The diameter of the cobalt bar is 3-5 mm.

[0030] Step 4) before the surface pretreatment, a lubricant is applied to the surface of the cobalt bar, the lubricant is a mixture of lubricating oil and chlorinated paraffin in a ratio of 1:1, the surface pretreatment temperature is 300-350°C, and the treatment time is 20-30min;

[0031] The deformation amount of each drawing pass is 10 to 18%;

[0032] The diameter of the cobalt wire is (1.00-2.00 mm) ± 0.003 mm;

[0033] The annealing temperature is 800-1000°C, the holding time is 20-30 minutes, and the vacuum is drawn to <1×10 -3 Pa.

[0034] Step 5) The electrolytic polishing is carried out in a NaOH solution with an alkali concentration of 6 to 9% wt, and the electrolysis current is 5 to 12 A;

[0035] The pay-off speed of the cobalt wire during electrolysis is 4-7 m / min;

[0036] The annealing temperature is 650-750°C, the holding time is 20-30 minutes, and the vacuum is evacuated to <1×10 -3 Pa.

[0037] Beneficial effects of the present invention:

[0038] (1) The method of the present invention uses cobalt powder reduction treatment to effectively remove free oxygen in the cobalt powder, reduce the effect of oxygen on the hot working brittleness of cobalt metal, and reduce the oxygen content of the cobalt wire.

[0039] (2) Zirconium powder is added during mixing, and high-energy ball milling is used to ensure the uniformity of powder particle size and improve the powder's molding ability. Zirconium powder plays a deoxidizing role during smelting and improves the processing plasticity of cobalt metal.

[0040] (3) In vacuum induction melting, step-by-step current adjustment and electromagnetic stirring are used to promote precise temperature control while ensuring uniform distribution of trace elements, which is conducive to the floating of impurities and reduces solidification shrinkage cavities in cobalt ingots.

[0041] (4) High temperature forging ensures the homogenization of the grain structure of the cobalt ingot and avoids the generation of cracks on the surface of the cobalt ingot; high temperature rotary forging further refines the grain structure inside the cobalt ingot and improves the uniformity of the grain structure; lubricants are used in the drawing process to avoid burrs and cracks on the surface of the cobalt bar during drawing.

[0042] The applicant's experiments verified that the method of the present invention can be used to prepare cobalt wire with a diameter of 1.00mm to 2.00mm, the purity of the cobalt wire is ≥99.95%, the content of each element of boron, cadmium, chromium, copper and silicon that are not resistant to radiation in the cobalt wire is ≤30ppm, the accuracy of the ellipticity of the cobalt wire reaches ±0.003mm, the surface roughness is ≤Ra1.6μm, the tensile strength is ≥900MPa, and the elongation is ≥6%.

[0043] The cobalt wires prepared by the method of the present invention all meet the performance requirements of emitter materials for self-powered neutron sensitive elements of EPR nuclear reactors. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0045] Further description is given below in conjunction with the accompanying drawings and specific implementation methods.

[0046] Embodiment 1:

[0047] See also Figure 1 , preparing a cobalt wire with a diameter of 2.00 mm, comprising the following steps:

[0048] 1) Cobalt powder reduction treatment:

[0049] Cobalt powder with a purity of 99.95% and a Fisher particle size of 15 to 35 μm was used. The cobalt powder was loaded into a molybdenum boat and placed in a hydrogen reduction furnace. The hydrogen flow rate was 4 L / min, the reduction temperature was 450°C, and the insulation time was 3 hours. The reduced cobalt powder was sieved through a 120-mesh sieve.

[0050] 2) Mixing and pressing:

[0051] The reduced cobalt powder is weighed 1500g, and the zirconium powder is weighed 2g. The weighed cobalt powder and zirconium powder are put into an agate ball mill for high-energy ball milling. The ratio of the mixture to the steel ball is 1:0.3. The high-energy ball milling time is 18h, and the speed is 120r / min. The mixed material after ball milling is put into a mold and pressed by a 500T hydraulic press. The pressing pressure is 200MPa and the pressure holding time is 15s. After demolding, a pressed cylindrical cobalt is obtained;

[0052] 3) Vacuum induction melting:

[0053] The cylindrical cobalt is placed in a zirconia crucible and placed in a vacuum melting furnace. Argon gas is introduced into the furnace for cleaning and then the vacuum is evacuated to 1.30×10 -3 Pa, gradually adjust the smelting current 5A ~ 30A, the current adjustment interval is 5min, each time the current is increased by 5A, until the cylindrical cobalt is completely melted, start electromagnetic stirring for 5min, and then lead the ingot into of cobalt ingots;

[0054] 4) Forging, rotary forging, drawing:

[0055] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt ingot, and the cobalt ingot is forged using a 200 kg air hammer. The heating temperature is 1000°C, the holding time is 15 minutes, the initial forging temperature is 1000°C, the final forging temperature is 750°C, and the deformation amount of each pass is 30%. The cobalt ingot is forged to of cobalt metal rods;

[0056] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt metal rod, and the cobalt metal rod is forged by a rotary forging machine. The heating temperature is 1000℃, the heat preservation time is 10min, and the deformation amount of each pass is 20%. The cobalt metal rod is forged to of cobalt bars;

[0057] The lubricant was applied on the surface of the cobalt bar, and the wire was drawn at 350°C for 30 min. The deformation of each drawing pass was 18%, and the cumulative deformation of the drawing process reached 90%. The cobalt wire was drawn to a diameter of 2.00 mm and vacuum annealed at 1000°C, holding time of 30 min, and vacuum degree of 2.1×10 -3 Pa;

[0058] 5) Electrolytic polishing and annealing:

[0059] The cobalt wire was electropolished in a NaOH solution with an alkali concentration of 9%wt, and the electrolysis current was 12A; the pay-off speed of the cobalt wire during electrolysis was 7m / min;

[0060] The electropolished cobalt wire was vacuum annealed at 750 °C, holding time 20 min, and vacuum degree 2.0 × 10 -3 Pa.

[0061] Embodiment 2:

[0062] See also Figure 1 , preparing a cobalt wire with a diameter of 1.50 mm, comprising the following steps:

[0063] 1) Cobalt powder reduction treatment:

[0064] Cobalt powder with a purity of 99.95% and a Fisher particle size of 15 to 35 μm was used. The cobalt powder was loaded into a molybdenum boat and placed in a hydrogen reduction furnace. The hydrogen flow rate was 6 L / min, the reduction temperature was 400°C, and the insulation time was 4 hours. The reduced cobalt powder was sieved through a 120-mesh sieve.

[0065] 2) Mixing and pressing:

[0066] The reduced cobalt powder is weighed to 1000 g, and the zirconium powder is weighed to 1.5 g. The weighed cobalt powder and zirconium powder are put into an agate ball mill for high-energy ball milling. The ratio of the mixture to the steel ball is 1:0.3. The high-energy ball milling time is 15 h, and the speed is 100 r / min. The mixed material after ball milling is put into a mold and pressed into shape by a 500T hydraulic press. The pressing pressure is 180 MPa, and the pressure holding time is 20 s. After demolding, a pressed cylindrical cobalt is obtained;

[0067] 3) Vacuum induction melting:

[0068] The cylindrical cobalt was placed in a zirconia crucible and placed in a vacuum melting furnace. Argon was introduced into the furnace for cleaning and then the vacuum was evacuated to 2.40×10 -3 Pa, gradually adjust the smelting current 5A ~ 30A, the current adjustment interval is 5min, each time the current is increased by 5A, until the cylindrical cobalt is completely melted, start electromagnetic stirring for 3min, and then lead the ingot into of cobalt ingots;

[0069] 4) Forging, rotary forging, drawing:

[0070] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt ingot. The cobalt ingot is forged using a 200 kg air hammer. The heating temperature is 950°C, the holding time is 15 minutes, the initial forging temperature is 950°C, the final forging temperature is 700°C, and the deformation amount of each pass is 25%. The cobalt ingot is forged to of cobalt metal rods;

[0071] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt metal rod, and the cobalt metal rod is forged by a rotary forging machine. The heating temperature is 950°C, the heat preservation time is 10 minutes, and the deformation amount of each pass is 18%. The cobalt metal rod is forged to of cobalt bars;

[0072] The lubricant was coated on the surface of the cobalt bar, and the wire was drawn after being treated at a temperature of 320°C for 25 minutes. The deformation amount of each drawing pass was 15%, and the cumulative deformation amount of drawing reached 80%. The cobalt wire with a diameter of 1.50 mm was drawn and vacuum annealed at 950°C, the holding time was 25 minutes, and the vacuum degree was 2.5×10 -3 Pa;

[0073] 5) Electrolytic polishing and annealing:

[0074] The cobalt wire was electropolished in a NaOH solution with an alkali concentration of 7%wt, and the electrolysis current was 8A; the pay-off speed of the cobalt wire during electrolysis was 6m / min;

[0075] The electropolished cobalt wire was vacuum annealed at 700 °C for 25 min and a vacuum degree of 2.2 × 10 -3 Pa.

[0076] Embodiment 3:

[0077] See also Figure 1 , preparing a cobalt wire with a diameter of 1.00 mm, comprising the following steps:

[0078] 1) Cobalt powder reduction treatment:

[0079] Cobalt powder with a purity of 99.95% and a Fisher particle size of 15 to 35 μm was used. The cobalt powder was loaded into a molybdenum boat and placed in a hydrogen reduction furnace. The hydrogen flow rate was 8 L / min, the reduction temperature was 350°C, the insulation time was 5 hours, and the reduced cobalt powder was sieved through a 120-mesh sieve.

[0080] 2) Mixing and pressing:

[0081] The reduced cobalt powder is weighed 700g, and the zirconium powder is weighed 0.5g. The weighed cobalt powder and zirconium powder are put into an agate ball mill for high-energy ball milling. The ratio of the mixture to the steel ball is 1:0.3. The high-energy ball milling time is 12h, and the speed is 80r / min. The mixed material after ball milling is put into a mold and pressed by a 500T hydraulic press. The pressing pressure is 150MPa and the pressure holding time is 15s. After demolding, a pressed cylindrical cobalt is obtained;

[0082] 3) Vacuum induction melting:

[0083] The cylindrical cobalt is placed in a zirconia crucible and placed in a vacuum melting furnace. Argon gas is introduced into the furnace for cleaning and then the vacuum is evacuated to 1.80×10 -3 Pa, gradually adjust the smelting current to 5A~25A, the current adjustment interval is 5min, and the current is increased by 5A each time until the cylindrical cobalt is completely melted, start electromagnetic stirring for 2min, and then lead the ingot into of cobalt ingots;

[0084] 4) Forging, rotary forging, drawing:

[0085] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt ingot. The cobalt ingot is forged using a 200 kg air hammer. The heating temperature is 900°C, the holding time is 15 minutes, the initial forging temperature is 900°C, the final forging temperature is 500°C, and the deformation amount of each pass is 30%. The cobalt ingot is forged to of cobalt metal rods;

[0086] A layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is coated on the surface of the cobalt metal rod, and the cobalt metal rod is forged by a rotary forging machine. The heating temperature is 1000℃, the heat preservation time is 10min, and the deformation amount of each pass is 20%. The cobalt metal rod is forged to of cobalt bars;

[0087] The lubricant was applied on the surface of the cobalt bar, and the wire was drawn at 650℃ for 25min. The deformation of each drawing process was 12%, and the cumulative deformation processing of drawing reached 70%. The cobalt wire with a diameter of 1.00mm was drawn and vacuum annealed at 900℃, holding time of 20min, and vacuum degree of 2.4×10 -3 Pa;

[0088] 5) Electrolytic polishing and annealing:

[0089] The cobalt wire was electropolished in a NaOH solution with an alkali concentration of 6%wt, and the electrolysis current was 5A; the pay-off speed of the cobalt wire during electrolysis was 5m / min;

[0090] The electropolished cobalt wire was vacuum annealed at 650 °C for 30 min and at a vacuum degree of 1.8 × 10 -3 Pa.

[0091] The wire diameter and ovality of the cobalt wire prepared in Example 1 to Example 3 were measured with a micrometer; the surface roughness of the cobalt wire was measured with a surface roughness meter; the tensile strength and elongation of the cobalt wire were tested with a microcomputer electronic universal testing machine; the surface quality of the cobalt wire was observed with a metallographic microscope, and the above measurement results are shown in Table 1; the purity and element impurity content of the cobalt wire were analyzed by chemical analysis and inductively coupled plasma spectrometer as shown in Table 2.

[0092] Table 1 Measurement results of Example 1-Example 3

[0093]

[0094] Table 2 Purity and element impurity content of cobalt wire in Example 1-Example 3

[0095]

[0096] Conclusion: The purity of the cobalt wires prepared by the method of the present invention in Examples 1-3 is ≥99.95%; the contents of boron, cadmium, chromium, copper and silicon in the cobalt wires are all less than 30ppm, and the contents of oxygen, nitrogen and hydrogen are all less than 100ppm, which have no effect on the performance of the cobalt wires; the precision of the ellipticity of the cobalt wires reaches 0.003mm; the surface roughness of the cobalt wires is no more than Ra1.6μm; the tensile strength of the cobalt wires is greater than 900MPa, and the elongation is greater than 6%; the surface of the cobalt wires is smooth and free of defects such as cracks and burrs. The cobalt wires prepared by the method of the present invention in Examples 1-3 meet the performance requirements of the emitter materials for the self-sufficient neutron sensitive elements of the EPR nuclear reactor.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification made to the present invention by those skilled in the art without departing from the spirit of the present invention shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a cobalt wire for a self-powered neutron sensitive element, characterized in that: The following steps are involved: 1) Cobalt powder reduction treatment: Using cobalt powder with a purity of ≥99.95% and a Fisher particle size of 15-35 μm, the cobalt powder is loaded into a molybdenum boat and reduced under hydrogen conditions at a reduction temperature of 350-550° C. and a heat preservation time of 3-5 hours to obtain reduced cobalt powder; 2) Mixing and pressing: The reduced cobalt powder is added to the zirconium powder for high-energy ball milling, and then pressed into shape after mixing. The amount of zirconium powder added is 0.1-0.3% of the weight of the cobalt powder; The purity of the zirconium powder is ≥99.99%; 3) Vacuum induction melting: The formed cobalt is placed in a vacuum melting furnace, and the melting current is gradually increased within the range of 0 to 30A, and the current adjustment interval is 2 to 5 minutes. After the cobalt is completely melted, electromagnetic stirring is performed for 2 to 5 minutes to form a cobalt ingot; 4) Forging, rotary forging, drawing: The cobalt ingot is forged into a cobalt metal rod, which is then rotary forged into a cobalt bar. After the surface of the cobalt bar is pretreated, the cobalt bar is drawn into a cobalt wire, which is then annealed. 5) Electrolytic polishing and annealing: The annealed cobalt wire is electropolished and annealed.

2. The preparation method according to claim 1, characterized in that: Step 1) The flow rate of hydrogen is 4 to 8 L / min.

3. The method for preparing cobalt wire according to claim 1, characterized in that: Step 2) The material-to-ball ratio of the high-energy ball mill is 1:0.3, the high-energy ball milling time is 12 to 18 hours, and the rotation speed is 70 to 130 r / min; The pressing pressure is 150-200 MPa, and the pressure is maintained for 15-30 seconds.

4. The method for preparing cobalt wire according to claim 1, characterized in that: Step 3) The formed cobalt is placed in a zirconia crucible and placed in a vacuum melting furnace; The vacuum melting furnace is firstly purged with argon gas and then evacuated to a temperature of <1×10 -3 Pa; The diameter of the cobalt ingot is 30-50 mm.

5. The method for preparing cobalt wire according to claim 1, characterized in that: Step 4) The heating temperature of the forging is 800-1000°C, the holding time is 8-15 minutes, the initial forging temperature is 900-1000°C, the final forging temperature is 650-750°C, and the deformation of each forging pass is 20-30%; Before the cobalt ingot is heated, a layer of high temperature resistant and anti-oxidation organic silicon lubricating coating is applied on its surface; The diameter of the cobalt metal rod is 13-15 mm.

6. The method for preparing cobalt wire according to claim 1, characterized in that: Step 4) The heating temperature of the rotary forging is 800-1000°C, the holding time is 5-10 minutes, and the deformation amount of each pass is 15-20%; Before the cobalt metal rod is heated, a layer of high temperature resistant and oxidation resistant organic silicon lubricating coating is applied on its surface; The diameter of the cobalt bar is 3-5 mm.

7. The method for preparing cobalt wire according to claim 1, characterized in that: Step 4) before the surface pretreatment, a lubricant is applied to the surface of the cobalt bar, the lubricant is a mixture of lubricating oil and chlorinated paraffin in a ratio of 1:1, the surface pretreatment temperature is 300-350°C, and the treatment time is 20-30 minutes; The deformation amount of each drawing pass is 10 to 18%; The diameter of the cobalt wire is (1.00-2.00 mm) ± 0.003 mm; The annealing temperature is 800-1000°C, the holding time is 20-30 minutes, and the vacuum is drawn to <1×10 -3 Pa.

8. The method for preparing cobalt wire according to claim 1, characterized in that: Step 5) The electrolytic polishing is carried out in a NaOH solution with an alkali concentration of 6 to 9%wt, and the electrolytic current is 5 to 12A; The pay-off speed of the cobalt wire during electrolysis is 4-7 m / min; The annealing temperature is 650-750°C, the holding time is 20-30 minutes, and the vacuum is evacuated to <1×10 -3 Pa.

Citation Information

Patent Citations

  • Preparation method and application of tissue-controllable ultrahigh-purity cobalt plate

    CN110923645A